2014
DOI: 10.1073/pnas.1312567111
|View full text |Cite
|
Sign up to set email alerts
|

Task context impacts visual object processing differentially across the cortex

Abstract: Perception reflects an integration of "bottom-up" (sensory-driven) and "top-down" (internally generated) signals. Although models of visual processing often emphasize the central role of feed-forward hierarchical processing, less is known about the impact of top-down signals on complex visual representations. Here, we investigated whether and how the observer's goals modulate object processing across the cortex. We examined responses elicited by a diverse set of objects under six distinct tasks, focusing on ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
152
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 158 publications
(179 citation statements)
references
References 76 publications
(79 reference statements)
22
152
5
Order By: Relevance
“…Accordingly, in human functional imaging, the strength of multivoxel codes in the MD system has been found to adjust according to task requirements, with perceptual discrimination increasing under conditions of high perceptual demand Woolgar, Hampshire, Thompson, & Duncan, 2011), rule discrimination increasing when rules are more complex (Woolgar, Afshar, Williams, & Rich, 2015), and a greater representation of visual objects that are at the focus of attention . These regions are also thought to make qualitatively different distinctions between visual stimuli in different task contexts (Harel, Kravitz, & Baker, 2014). The data presented here emphasize the extent of flexibility in these regions, suggesting that they are capable of representing task relevant information from visual, auditory, rule, and motor domains.…”
Section: Discussionmentioning
confidence: 55%
“…Accordingly, in human functional imaging, the strength of multivoxel codes in the MD system has been found to adjust according to task requirements, with perceptual discrimination increasing under conditions of high perceptual demand Woolgar, Hampshire, Thompson, & Duncan, 2011), rule discrimination increasing when rules are more complex (Woolgar, Afshar, Williams, & Rich, 2015), and a greater representation of visual objects that are at the focus of attention . These regions are also thought to make qualitatively different distinctions between visual stimuli in different task contexts (Harel, Kravitz, & Baker, 2014). The data presented here emphasize the extent of flexibility in these regions, suggesting that they are capable of representing task relevant information from visual, auditory, rule, and motor domains.…”
Section: Discussionmentioning
confidence: 55%
“…Although some studies reported higher FFA responses to objects of expertise than control objects (Gauthier et al, 2000;Xu, 2005), consistent with this hypothesis, these effects were small and many other studies failed to replicate them (Grill-Spector et al, 2004;Op de Beeck et al, 2006;Yue et al, 2006). Further, in all studies that have looked, expertise effects are not restricted to the FFA, but extend to multiple other brain regions (Gauthier et al, 2000;Harel et al, 2010;McGugin et al, 2012;Harel et al, 2014), as expected if these effects simply reflect greater attentional engagement by objects of expertise (Harel et al, 2010). Thus, there is no replicable evidence for a special linkage between the FFA (or face selectivity in general) and expertise.…”
Section: Introductionmentioning
confidence: 81%
“…The representational geometry of a brain region has recently been shown to be somewhat influenced by top-down mechanisms such as attention and behavioural goals (Çukur, Nishimoto, Huth, & Gallant, 2013;Harel, Kravitz, & Baker, 2014;Rogers et al, 2006;Tyler et al, 2004). Çukur et al (2013) used fMRI to study the impact that searching for an object category during a natural movie has on the semantic representation measured in the brain.…”
Section: From Stable To Task-flexible Representationsmentioning
confidence: 99%
“…Using voxel-wise modelling and regularised regression, the authors showed how attending one category distorted the semantic structure of the neural representations of both attended and unattended categories, with categoryattended expansion of the representational geometry at the Language, Cognition and Neuroscience 371 cost of a compression of the distant category (Çukur et al, 2013). In another study, Harel et al (2014) used fMRI to investigate how the neural representations in regions of the ventral temporal cortex vary as a function of task. They compared the brain-activity patterns for a single set of objects under six different tasks (fixation, colour, tilt, content, movement and size).…”
Section: From Stable To Task-flexible Representationsmentioning
confidence: 99%